PIRÂMIDE DE VEGETAÇÃO COMO BASE PARA ESTUDO BIOGEOGRÁFICO NA MICRORREGIÃO DE BOQUIM/SE - Silva, Alda Lisboa de Matos (2019)
The article's structure is based on the importance of nature for society, since this relationship has generated impacts, lack of control and imbalance. The central object considers the analysis of vegetation in its composition in the Boquim - SE Microregion, considering the landscape units, their biophysical characteristics, territorial suitability and cultural manifestations. It is part of a doctoral thesis. Finally, the construction of vegetation pyramids is considered operational, as an analysis sample to evaluate evolution, balance, progression and regression of strata in soil dynamics, soil climate exposure, slope, geology and anthropic action. Finally, the basis for understanding the regional environmental dynamics.